2004
DOI: 10.1590/s0103-50532004000600003
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric determination of dipyrone using a N,N'-ethylenebis(salicylideneaminato)oxovanadium(IV) modified carbon-paste electrode

Abstract: A preparação e a caracterização eletroquímica de um eletrodo de pasta de carbono modificado com o complexo N, N´-etilenobis(salicilidenoaminato) de oxovanádio(IV) ([VO(Salen)]), como também o seu comportamento eletrocatalítico na oxidação da dipirona foi investigado. O comportamento eletroquímico do eletrodo modificado e a eletrooxidação da dipirona foram estudados usando a voltametria cíclica. A resposta voltamétrica do eletrodo modificado é baseada em duas reações. Uma relacionada com a oxidação eletroquími… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 16 publications
2
27
0
1
Order By: Relevance
“…An irreversible two-electron oxidation voltammetric peak appeared in both cases when 0.005 mol L -1 SMX was present in the solution [29,40]. Also, much lower background current that was obtained for the CPE as compared with the solid glassy carbon, suggests that the proposed CPE electrode could be more sensitive for SMX oxidation [6][7][8][9][10][11][12][13][14][15][16]. The higher background current observed for the glassy carbon electrode in Figure 5B stems from the oxygen evolution [43].…”
Section: Electrochemical Properties Of Cpe In Different Electrolyte Smentioning
confidence: 90%
See 2 more Smart Citations
“…An irreversible two-electron oxidation voltammetric peak appeared in both cases when 0.005 mol L -1 SMX was present in the solution [29,40]. Also, much lower background current that was obtained for the CPE as compared with the solid glassy carbon, suggests that the proposed CPE electrode could be more sensitive for SMX oxidation [6][7][8][9][10][11][12][13][14][15][16]. The higher background current observed for the glassy carbon electrode in Figure 5B stems from the oxygen evolution [43].…”
Section: Electrochemical Properties Of Cpe In Different Electrolyte Smentioning
confidence: 90%
“…The following electrolyte solutions were used in this research: 0.1 mol L -1 potassium chloride (Synth), 0.1 mol L -1 sodium nitrate containing 0.01 mol L -1 potassium ferricyanide, 0.1 mol L -1 sodium perchlorate; 0.05 mol L -1 sulfuric acid (Merck)/methanol in 70:30 % (v/v) ratio and 0.04 mol L -1 BrittonRobinson (BR) buffer, pH 2.18, prepared by mixing 0.04 mol L -1 boric acid (Carlo Erba), acetic acid and orthophosforic acid (Merck). Mixtures of graphite powder (particle size = 19.2-168.5 µm, Analítica) and mineral oil (Nujol, União Química) were used to prepare the carbon paste [14,16].…”
Section: Materials and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perez-Ruiz et al 41 also observed the same electrochemical behavior for dypirone using a glassy carbon electrode and a carbon paste electrode respectively. According to Teixeira et al, 45 the first electrochemical oxidation peak of the dypirone is related to the methylamino-Nmethanesulphonate group.…”
Section: Cyclic Voltammetric Study Of Paracetamol and Dypirone With Cmentioning
confidence: 99%
“…DIP has also been determined in pharmaceutical formulations by HPLC, 4,5 UV-Visible spectrophotometry, [6][7][8][9][10] turbidimetry, 11 chemilumimetry, 12,13 amperometry 14 and voltammetry. 15,16 The most of these methods involve cumbersome steps, such as derivatization reactions, previous separations, solvent extraction, or sample filtration. Vol.…”
Section: Introductionmentioning
confidence: 99%